Necrotizing Pneumonia: A Practical Guide for the Clinician - Esha Madhu Kapania; Rodrigo Cavallazzi (Pathogens)
While rare, necrotizing pneumonia is a severe and potentially life-threatening manifestation of lung parenchyma infection. Initially documented in the 1940s, it was a significant contributor to mortality rates in both adults and children, with figures reaching up to 45%. Despite being a disease described in the literature for decades, data on the management of necrotizing pneumonia remain limited. Most available information comes from retrospective observational cohort studies. This article aims to provide a comprehensive summary of the existing literature on the subject.